DECISION-MAKING IN ADOLESCENTS AT RISK FOR NON-SUICIDAL SELF-INJURY (NSSI) BEHAVIOR - Aisha, Dinda; Rahman, Puspa Rahayu Utami; Putrie, Cempaka (Psikoislamedia: Jurnal Psikologi, 2025)
Non-Suicide Self Injury (NSSI) or self-harm is being widely discussed and conducted by adolescents in Indonesia. This study was conducted on adolescents in Karawang using 3 measuring instruments, GDMS, DERS-18 and Father Involvement Scale. The purpose is to determine the dynamics of decision making in adolescents who have a tendency to commit NSSI. The population in this study was 116 adolescents age range 12-21 years who live in Karawang. The analysis used JASP by looking at path analysis both directly and indirectly. Decision making is divided into 5 types. The results is a direct influence of spontaneous decision making on NSSI. Showing that individuals who have a tendency to make decisions quickly and without thinking carefully are at higher risk of committing NSSI. Furthermore, emotional regulation plays an important role in mediating the influence of other decision making on NSSI. And also mediates the influence of father involvement on NSSI.